Distinct biotite‐weathering activities of Arthrobacter pascens F74 under different contact conditions. (16th December 2019) - Sun, Yue; Wang, Yuanli; Li, Lei; Sun, Lijing; He, Linyan; Sheng, Xiafang
Abstract: Bacteria play important roles in mineral weathering and soil formation. However, little is known regarding the interactions between biotite and Arthrobacter strains. In this study, the mineral–mineral activities of the Arthrobacter pascens F74 isolated from a weathered rock surface were evaluated for its weathering behavior under direct contact and no contact with biotite. No contact was obtained by using dialysis bags. When directly in contact with biotite, Al and Fe concentrations increased by 9‐ to 47‐fold compared with the controls in the presence of strain F74. Furthermore, strain F74 increased mobilized Al by 106% to 175% and Fe by 29% to 123% under direct contact than under no contact conditions. During biotite dissolution, significantly higher cell numbers and lower pH in the culture medium were observed in the presence of strain F74 under direct contact conditions than under no contact conditions. Significantly higher gluconic acid concentration and glucose dehydrogenase activity were found under direct contact conditions than under no contact and no biotite conditions. Scanning electron microscopy analysis showed cell adhesion on the biotite surface. These results demonstrated that strain F74 behaved differently with respect to biotite‐weathering effectiveness and mechanisms under different contact conditions. The results also suggested that direct contact between biotite and strain F74 was important for the production of gluconic acid, cell adhesion on the mineral surface, and the mineral dissolution of the strain.